Herencia de la reacción a roya del tallo y roya de las glumas en los cruces recíprocos de los trigos 'Reward-H44-Rhodesian C.12273' y 'Barleta Benvenuto', en condiciones de la Sierra del Perú - Villanueva Novoa, R.; Calderón Pérez, G. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The Inheritance of several characters was studied in a reciprocal class between two wheat varieties. ‘Barleta-Benvenuto’ and ‘Reward-H44-Rhodesian C. 12273’ in Cuzco (Peru) (2910 m above sea level). ‘Barleta-Benvenuto’ is an Argentine wheat, awned and very susceptible to stem and stripe rusts. ‘Reward-H44-Rhodesian C. 12273’ is a Peruvian wheat awnleted and resistant to stem and stripe rust. The inheritance of the length of the awn took place in the ratio of 3.1 for awnleted to awned plants. The inheritance of reaction to stem rust took place in the ratio of 9.3.4 for resistant, semiresistant and susceptible plants. The inheritance of reaction to yellow rust took place in the ratio of 12.3.1 for resistant, semiresistant, and susceptible plants. There was tendency to some association, probably genetical, between reaction to stem rust and stripe rust, reaction to stem rust and grain number per head, and reaction to stem rust and grain weight per head. There was no tendency to association between: reaction to stem rust and tillering; reaction to stripe rust and tillering; reaction to stripe rust and grain number per head, and reaction to stripe rust and grain number per head.